2022
DOI: 10.1002/marc.202200301
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress in Polypeptoids Prepared by Controlled Ring‐Opening Polymerizations

Abstract: Polypeptoids, structural mimics of polypeptides, have attracted considerable attention due to their biocompatibility, proteolytic stability, thermal processability, good solubility, synthetic accessibility, and structural diversity. Polypeptoids have emerged as an interesting material in both polymer science and biological field. This review primarily discusses the research progress of polypeptoids prepared by controlled ring‐opening polymerizations in the past decade, including synthetic strategies of monomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 92 publications
(209 reference statements)
0
5
0
Order By: Relevance
“…Polypeptoids can be readily created using different preparation methods. In addition to the solid-phase submonomer synthesis method, which affords short-chain polypeptoids, ring-opening polymerization (ROP) has become an effective way of producing high-molecular-weight polypeptoids with different structures in good yields [ 27 , 28 ]. Micelles constructed from polypeptoids, especially those with stimuli-responsive properties, have great application potential yet are underexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Polypeptoids can be readily created using different preparation methods. In addition to the solid-phase submonomer synthesis method, which affords short-chain polypeptoids, ring-opening polymerization (ROP) has become an effective way of producing high-molecular-weight polypeptoids with different structures in good yields [ 27 , 28 ]. Micelles constructed from polypeptoids, especially those with stimuli-responsive properties, have great application potential yet are underexplored.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, synthetic methods to produce well-defined polypeptoids with a range of Nsubstituent structures have been well established. 28,29 Previous studies by Zuckermann and co-workers have shown that polypeptoids with an optimized sequence and N-substituent structures can adopt an extended conformation at oil/water interfaces. 30,31 Servoss and co-workers have demonstrated that facially amphiphilic sequence-defined peptoid helices preferentially interact with the edges of phospholipid-based bicelles.…”
Section: ■ Introductionmentioning
confidence: 99%
“…), and the polypeptoid backbone conformation can be tailored by the N -substituent structure. In addition, synthetic methods to produce well-defined polypeptoids with a range of N -substituent structures have been well established. , Previous studies by Zuckermann and co-workers have shown that polypeptoids with an optimized sequence and N -substituent structures can adopt an extended conformation at oil/water interfaces. , Servoss and co-workers have demonstrated that facially amphiphilic sequence-defined peptoid helices preferentially interact with the edges of phospholipid-based bicelles . Most recently, an amphiphilic peptoid oligomer with a total of 15 residues arranged in a repeating pattern of two N -2-ethylphenyl glycine followed by one N -2-ethyl carboxyl glycine unit has been synthesized and used to stabilize lipid nanodiscs containing the Pf1 coat protein.…”
Section: Introductionmentioning
confidence: 99%
“…This stepwise approach is limited in the accessible chain length (typically degree of polymerization <50) and synthetic scalability. By contrast, controlled ring-opening polymerizations of N -substituted glycine derived N -carboxyanhydride have been developed to enable access to well-defined polypeptoid BCPs with long average chain lengths and controlled block sequences, notwithstanding the inherent chain length and compositional dispersity. , Our earlier studies of sequence-defined peptoid diblock copolymers with a discrete chain length have revealed that the position and number of charged monomers along the chain can modulate the aggregation number and size of spherical micelles in aqueous solution in a highly predictable manner. , Separately, the coupled charge and aromatic residue pattern has been shown to influence the chain conformation and stability of sequence-defined peptoid micelles with lamellar or spherical geometry . In comparison, it remains ambiguous regarding whether the charge pattern encoded in the block sequences of ionic BCP obtained by controlled polymerization methods can effectively modulate the polymer association to form micelles with distinct structural characteristics, considering the statistical variation of chain length and composition inherent to these BCP that may smear the effect of the charge pattern.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, controlled ring-opening polymerizations of N -substituted glycine derived N -carboxyanhydride have been developed to enable access to well-defined polypeptoid BCPs with long average chain lengths and controlled block sequences, notwithstanding the inherent chain length and compositional dispersity. 39 , 48 Our earlier studies of sequence-defined peptoid diblock copolymers with a discrete chain length have revealed that the position and number of charged monomers along the chain can modulate the aggregation number and size of spherical micelles in aqueous solution in a highly predictable manner. 9 , 11 Separately, the coupled charge and aromatic residue pattern has been shown to influence the chain conformation and stability of sequence-defined peptoid micelles with lamellar or spherical geometry.…”
Section: Introductionmentioning
confidence: 99%